Keadilan Organisasi dan Komitmen Organisasional terhadap Kepuasan Kerja Pegawai di Kantor Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Aminar Sutra Dewi; Tiara Elka Savitri (Manajemen Kreatif Jurnal, 2024)
The aim of this research is to determine the dominant indicators of the variables Employee Job Satisfaction, Organizational Justice and Organizational Commitment in the Population and Civil Registration Service of Padang City and to determine the partial influence of Organizational Justice and Organizational Commitment on employee job satisfaction in the Population and Civil Registration Service Padang city. This type of research is quantitative, the sampling technique used is a total sampling technique which is taken based on the entire population, because the population is less than 100 people. The research sample consisted of 46 people. The types of data used in this research are primary data and secondary data. The technique for analyzing the data uses validity and reliability tests using the SPSS version 21.00 program. The hypothesis was tested using the T test. The results of this research show (1) Organizational Justice has a significant effect on employee job satisfaction at the Padang City Population and Civil Registration Service (2) Organizational Commitment has a significant effect on employee job satisfaction at the Padang City Population and Civil Registration Service. This research aims to determine the dominant indicators of employee job satisfaction variables.